Subtitling Analysis Of Noun Phrases In Madagascar 3 Movie - Widyaningsih, Mutiyah Nuraini, Dra. Dwi Haryanti, M. Hum, Siti Fatimah, S. Pd M.Hum (2013)
This research focused on translation shift. The objectives of this study are to classify the translation shift of noun phrase and to describe the equivalence translation of noun phrase in Madagascar 3 Movie. This research belongs to a descriptive qualitative study which takes a document oriented as the method of collecting data. As the data source, the reseracher uses Madagascar 3 movie and its subtitle, and the data are sentences that containing noun phrase on Madagascar 3 movie which happened translation shift. The results of this research show that translation shift There are 2 translation shift of noun phrase in the Madagascar 3 movie subtitle, they are, level shift and category shift. First, the researcher divides level shift of noun phrase into 6 types. From 164 data, the researcher finds 105 data or 64.02% of noun phrases are subtitled into noun, 6 data or 3.66% of noun phrases into verb, 5 data or 3.05% of noun phrases into pronomina, 5 data or 3.05% of noun phrases into adjective, 3 data or 1.83% of noun phrases into adverb, and 1 datum or 0.61% of noun phrase is subtitled into clause. Second, the researcher divides category shift of noun phrase into 5 types. From 164 data, the researcher finds 4 data or 2.44% of noun phrases are subtitled into verb phrase, 3 data or 1.83% of noun phrases into prepositional phrase, 9 data or 5.49% of noun phrases into adverb phrase, 2 data or 1.22% of noun phrases into adjective phrase, and 21 data or 12.80% of noun phrases are omitted. The equivalence of translation divided into equivalent translation and non equivalent translation. From 164 data, there are 157data or 95.73% equivalent translation. Beside, the researcher finds 7 data or 4.27% of 164 data of non equivalent translation.